EFFECT OF REPRODUCTIVE STAGES ON SOME BLOOD METABOLITES IN THE SHOW AND RACEHORSE MARES IN IRAQ - M. A. Abed; T. A. Abdulkareem; W. A. Saleh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study explored the effect of different reproductive stages on some blood metabolic biomarkers of the show and racehorse mares in Iraq. We selected eighteen show mares and fifteen racehorse mares and divided them into three categories: last month of pregnancy, post-foaling, and first month of pregnancy. Blood samples were collected twice via jugular venipuncture, and blood biochemical metabolic biomarkers were evaluated by gas chromatography (GC) and high liquid chromatography (HPLC). A significant (P≤0.05) increase was observed for the concentration of serum glucose and creatine of pregnant show horse mares in the last month compared to the remaining stages. Serum fatty acid concentrations were numerically higher in the last month than in the remaining stages. Showhorse mares were higher than racehorse mares for all stages. The differences observed in serum non-esterified fatty acids for all stages and the show and racehorse mares lacked significance. The racehorse mares exhibited higher (P≤0.05) serum concentrations of total protein than those of the showhorse mares. For both types, serum total protein was higher (P≤0.05) in the first and last month than in the post-foaling period. In conclusion, some blood metabolites differ according to reproductive stages and mare types and can considered for diagnosing diseases and determining nutritional requirements for each type and reproductive stage.